2022
DOI: 10.4110/in.2022.22.e21
|View full text |Cite
|
Sign up to set email alerts
|

As a Modulator, Multitasking Roles of SIRT1 in Respiratory Diseases

Abstract: As far the current severe coronavirus disease 2019 (COVID-19), respiratory disease is still the biggest threat to human health. In addition, infectious respiratory diseases are particularly prominent. In addition to killing and clearing the infection pathogen directly, regulating the immune responses against the pathogens is also an important therapeutic modality. Sirtuins belong to NAD+-dependent class III histone deacetylases. Among 7 types of sirtuins, silent information regulator type-1 (SIRT1) played a mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 136 publications
2
7
0
Order By: Relevance
“… 33 Recently, it has been demonstrated that IL-22-induced proliferation and inflammation of keratinocytes is negatively regulated by SIRT1 through deacetylation of STAT3. 6 In this study, we also found increased STAT3 acetylation in psoriatic lesions. However, restoration of intracellular NAD + content by treatment with dunnione resulted in the downregulation of STAT3 acetylation through increased SIRT1 activity.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“… 33 Recently, it has been demonstrated that IL-22-induced proliferation and inflammation of keratinocytes is negatively regulated by SIRT1 through deacetylation of STAT3. 6 In this study, we also found increased STAT3 acetylation in psoriatic lesions. However, restoration of intracellular NAD + content by treatment with dunnione resulted in the downregulation of STAT3 acetylation through increased SIRT1 activity.…”
Section: Discussionsupporting
confidence: 71%
“… 29 Remarkably, SIRT1 physically interacts with nuclear translocated NF-κB p65 and deacetylates NF-κB p65 at residue Lys-310, inhibiting the transcriptional activity of NF-κB. 6 In this study, we also observed elevated NF-κB p65 acetylation in IMQ-treated skin lesions, which was facilitated by reduced SIRT1 activity induced by decreased intracellular NAD + levels. However, the increase in the cellular NAD + levels by NQO1 by dunnione resulted in downregulation of NF-κB p65 acetylation in the skin lesions, as well as production of inflammatory cytokines through increased SIRT1 activity.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Respiratory diseases are one of the biggest threats to human health. 590 Common respiratory diseases, including asthma, chronic obstructive pulmonary disease (COPD), lung fibrosis (LF), coronavirus disease 2019 (COVID-19), and other lung injures, seriously affect physical and mental health. 590 SIRTs have received considerable attention due to their important effects on respiratory diseases.…”
Section: Introductionmentioning
confidence: 99%